[PP.11.10] CYSTATIN C AND ITS ASSOCIATION WITH CAROTID PLAQUE AND INTIMA MEDIA THICKNESS IN SUBJECTS WITHOUT KNOWN CARDIOVASCULAR AND KIDNEY DISEASES. (September 2016) - Maloberti, A.; Farina, F.; Varrenti, M.; Vallerio, P.; Musca, F.; Belli, O.; Panzeri, F.; Peretti, A.; Palazzini, M.; Zanni, F.; Casadei, F.; Facchetti, R.; et al.
Abstract : Objective: Cystatin-C was reported to be a surrogate of kidney function while a high level of this marker has been shown to be a strong predictor of CardioVascular (CV) events in patients with Chronic Kidney Disease (CKD). It has also been shown to correlates with CV events and with carotid plaque and preclinical atherosclerosis (i.e. Intima Media Thickness – IMT) in patients without CKD or known CV risk factors, although these results have not been confirmed by recent studies. The present work is aimed at assessing the association between cystatin-C and carotid atherosclerosis in a population free of CKD and CV diseases. Design and method: We studied 480 healthy and normotensive blood donor subjects. We evaluated common carotid IMT and plaques by ultrasound (Philips 5500, 7.5 Hz Probe) together with office Blood Pressure (BP). Cystatin-C was measured on plasma (ELISA methods); blood glucose, total, HDL and LDL cholesterol were also measured. Results: 2.5% of the population (12 subjects) showed an IMT higher than 0.9 mm. Those subjects were older (53.1 ± 7.5 vs 44.7 ± 9.6 years, p < 0.001) and showed a significantly higher plasma glucose (97.6 ± 19.2 vs 89.6 ± 10.6 mg/dL, p = 0.01) and Cystatin-C levels (0.72 ± 0.29 vs 0.62 ± 0.13 mg/L, p < 0.05) than subjects with IMT < 0.9 mm. 8.9% of the population (43 subjects) had carotid plaque. Those subjects were older (52.7 ± 7.6 vs 44.9 ± 9.6 years, p < 0.001) and showed higher plasma glucose (94.4 ± 12.7 vs 89.8 ± 11.1 mg/dL, p = 0.01) total and LDL cholesterol (Total ch:208.1 ± 29.4 vs 195.3 ± 32.6 mg/dL, p = 0.08; LDL ch:132.8 ± 27.6 vs 122.1 ± 30.4 mg/dL, p = 0.01) and Cystatin-C levels (0.69 ± 0.12 vs 0.62 ± 0.13 mg/L, p < 0.05) than subjects without plaques. In every case statistical significance survived to age correction. Plasma levels of Cystatin-C linearly significantly and positively correlated with traditional risk factors, i.e. age (r = 0.17, p < 0.001), waist circunference (r = 0.23, p < 0.001), IMT (r = 0.16, p = 0.002), SBP (r = 0.14, p = 0.001), glucose (r = 0.12, p = 0.005) and creatinine (r = 0.11, p < 0.001), while negatively with HDL cholesterol (r = −0, 21, p < 0.001). The independent predictors of Cystatin-C levels at multivariate analysis were IMT (β = 0.02, p = 0.005), waist circonference (β = 0.07, p < 0.001) and HDL cholesterol (β = 0.02, p = 0.01). Conclusions: Our results suggest that in healthy subjects without CKD with carotid OD cystatin-C is increased, well reflecting arterial damage also in absence of essential hypertension or CKD. In healthy normotensive blood donors Cystatine-C is a marker of the atherosclerotic process and well correlates with traditional risk factors.